Judging interpretations - Hershovitz, S (2001)
Interpretation is fashionable, and not just in jurisprudence. Yet for all the attention interpretation has received in the past few decades, we have a poor understanding of what it is and what counts as doing it well. This thesis begins with the question, ‘What is interpretation?’ I argue that the reigning orthodoxy which holds that interpretation seeks meaning is misguided. A more illuminating account of interpretation is developed on which interpretation seeks understandings. After explaining what interpretation is and how it works, I explore the norms which govern it. As part of this exploration, I expose a number of mistakes in Stanley Fish’s account of the nature of interpretive constraints. Ib then develop an alternative account of what it means to say that objects (including texts) constrain their own interpretation, and I show that they often do so. I outline a view of interpretation I call almost pragmatism according to which the appropriate standards for judging an interpretation vary with the purpose for making the interpretation. I also argue that legal theorists have misunderstood and misapplied Ludwig Wittgenstein’s remarks on rules and interpretation in a variety of ways. I conclude that there is nothing useful we can learn about law from Wittgenstein’s remarks on rules. The second part of this thesis uses the improved understanding of interpretation developed in the first part to shed light on problems which have long perplexed students of jurisprudence. I begin by considering what standards should be used to assess judicial interpretation. I argue that the appropriate standards to use will properly vary among different legal systems, and thus general jurisprudence can contribute little to the debate. Two general suggestions for norms which might govern legal interpretation—fidelity to legislative intent and Ronald Dworkin’s best light requirement—are taken up in the final chapters. In preparation for the final chapters, I summarize Joseph Raz’s account of authority, which forms the basis of many of the arguments to be considered. I suggest that Raz’s account of legitimacy is inadequate for understanding the legitimacy of political authorities. I then turn to arguments Raz offers suggesting that, in a limited sense, judicial interpretations ought to be judged according to their fidelity to legislative intent. I contend that Raz is wrong in thinking that we must interpret in accord with the intention of law-makers in order to make sense of their authority. The final chapter examines Dworkin’s best light requirement. I present an understanding of its content and scope consistent with what we learned about interpretation in the opening chapters and consider important objections to it. I conclude that Dworkin’s interpretive method is not inconsistent with law’s authority, as Raz and others have maintained.